The effect of mayoral attributes on the financial performance of selected municipalities for improved service delivery in South Africa - Rapholo, Matau Gladys (My University, 2021)
This study investigated the effect of mayoral attributes on the financial performance of selected municipalities for improved service delivery in South Africa. The study adopted the quantitative research method to examine the relationship between mayoral attributes (age, administrative experience, and educational background) and financial performance. This study used data from 30 municipalities based in the Limpopo Province of South Africa. The study used data collected from selected municipal annual reports available on their websites using purposive sampling and panel data analysis to analyse the data. The results showed a positive relationship between administrative experience and financial performance, a negative relationship between age and financial performance, and a negative relationship between educational background and financial performance. Therefore, the study recommends that to improve financial performance in municipalities for improved service delivery the appointment of a municipal mayor should be based on administrative experience. Furthermore, the study suggests that in consideration of the need to interpret constantly emerging new financial regulations to promote financial stability in municipalities, the educational qualifications of mayoral candidates should be prioritised. However, the study did not examine other mayoral attributes that can affect financial performance, such as independence, race, and allowance because they are challenging to estimate. Keywords: Financial performance; age; Administrative experience; Educational background; municipalities; mayoral attributes.
Thesis (M. Com. (Accountancy)) -- University of Limpopo, 2021
Keywords: Financial performance; Age; Administrative experience; Educational background; Municipalities; Mayoral attributes; Municipal government; Municipal finance -- Accounting